Development of Computer-Based Learning Media (Digital) Tutorial Model to Improve Physics Learning Process in the Pandemic Era (Covid-19) - Listiani, Tia; Nurhasanah, Nurhasanah; Hidayat, Rahmat; Alamuna H, Saosan Alamuna H; Septiana, Tasya; Watin, Wisnu; Walihah, Zahratul; Susilawati, Susilawati (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
The purpose of the research from the results of the review of 25 journals is to determine the feasibility of computer-based (digital) learning media that can be used by teachers as learning media using a tutorial model. Research from the results of a review of 25 journals uses the R&D (Research and Development) method that produces products from researchers. Based on the results of the reviews of several journals, the average percentage of eligibility from the validation results of material experts, media experts, and test results can be said to be in a good category and feasible to use, so that it can be used as a reference for prospective teachers to increase knowledge in learning techniques, improve learning outcomes. students and motivate students in the learning process in the Covid-19 era